PENGARUH CITRA MEREK DAN PENGALAMAN KONSUMEN TERHADAP LOYALITAS KONSUMEN SEPATU SNEAKER MEREK CONVERSE (STUDI KASUS PADA PENGGUNA SEPATU SNEAKER MEREK CONVERSE DI KOTA SEMARANG) - Aldo Dwi Wicaksono; Hari Susanta Nugraha (Universitas Diponegoro, 2017)
Every company expect to have a high customer loyalty. But, there is a Converse sneakers product sales degression in Semarang City based on observation that also indicate a degression in customer loyalty. Based on observation and theoritical study, that degression supected caused by low brand image factor and low customer experience factor. Therefore, the purpose of this research is to find out the impacts of brand image and cutomer experience towards Converse sneakers cutomer loyalty, both in partial and simultant.Amount of the samples in this research is 100 respondents that were taken using accidental sampling technic. To the respondents given a questionnaire in periode between 17-31 Augustus 2016. The statistic analyst instrument that used in this research is partial regression and simultant regression.After editing, coding, and tabulation, this research results these conclution: 1) Brand image positively and significantly impacts on Converse sneakers cutomer loyalty, 2) Customer experience positively and significantly impacts on Converse sneakers customer loyalty. 3) Brand image and customer experience simultaneously impacts on Converse sneakers customer loyalty.